The RIFLE Classification: A Stratification Scheme for Patients of Acute Renal Failure after Coronary Artery Bypass Surgery - Idris, Rumman; Khan, Musa; Kamruzzaman, Md; Hannan, Abdul; Kabir, Humayun; Jahan, Nusrat (Cardiovascular Journal, 2022)
Background: Acute renal failure is linked to an increased risk of death and morbidity after cardiac surgery. Because there are no standard criteria for acute renal damage, there is a wide variation in the reports that have been published. The Acute Dialysis Quality Initiative Workgroup has developed new RIFLE criteria for acute renal dysfunction. The goal of current study was to appraise whether this definition of postoperative renal dysfunction after coronary artery bypass surgery (CABG) was accurate. Methods: Fifty patients with critical coronary artery disease & undergoing CABG were enrolled in the study. Out of 50 patients, 25 patients had CABG with cardiopulmonary bypass (CPB) and remaining 25 underwent off pump CABG (OPCAB). Patients were distributed into various groups (based on the severity of renal impairment) using the RIFLE classification: Risk, Injury, Failure, Loss, End-stage kidney disease) depending on either serum creatinine level/ estimated glomerular filtration rate (eGFR) or urine output. The variation with 30 days-mortality, ICU stay and renal replacement therapy after CABG were identified. Results: After CABG, 10% of patients experienced renal impairment, as per definitions of RIFLE classification. In this study, there is no significant difference in ARF (RIFLE classification-normal and risk) with or without use of CPB. However, incidence of RIFLE- injury and failure is higher in CPB group than no CPB group. The postoperative proportions of death and renal failure necessitating renal replacement therapy (RRT) were 2% (number of patients, 1 of 50) and 2% (1 of 50), respectively in RIFLE-failure. For the whole study cohort, the median duration of postoperative ICU stay was 4.0 days, with interquartile ranges of 3.0 to 7.0 days. All the patients of Rifle classification-injury and failure had prolonged ICU stay (5 or more days). Conclusions: The RIFLE criteria are a useful tool for determining renal impairment after CABG. Increased renal replacement treatment, longer ICU stays, and a higher death rate are all linked to the severity of RIFLE classification. Cardiovasc j 2022; 14(2): 150-156